Pemanfaatan Media Sosial Yang Cerdas dan Berakhlak Untuk Meningkatkan Kreatifitas Pelajar Rumah Yayasan Bening Nurani Padang. - Wijaya, Anggi Hadi; ., Syamsi; Azmi, Khairil (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
Social media seems to have become an addiction for Indonesian people, especially teenagers. Today's teenagers are synonymous with smartphones in their hands almost 24 hours a day. The social media most often used by teenagers include Facebook, Twitter, Path, YouTube, Instagram, Line and Whatsapp. Social media has its own advantages and interests for its users. Social media offers many conveniences that make teenagers feel at home using it for a long time. The emergence of various types of social media has had both positive and negative influences. To prevent negative impacts, for example the spread of hoax news and hate speech expressed by haters from becoming more widespread, the government has made a number of revisions to the articles and paragraphs in the Information and Electronic Transactions Law (UU ITE). With the existence of several deviations or misuse of social media itself, it is felt necessary to provide socialization to teenagers in responding to and using social media intelligently and with morals. So that social media can be useful for developing the creativity of Islamic youth at the youth level, especially at the Bening Conscience Foundation House in Padang